Homosexuality and perversion in the field of psychoanalysis - Richard Harrison Couto; Tayane dos Santos Lage (Semina: Ciências Sociais e Humanas, 2018)
In the field of psychoanalysis there is still confusion about homosexuality and perversion. It is not uncommon to see homosexuality included by many in the field of perversions. Especially in Freud’s works, where some authors mention that Freud refers to homosexuality as an example of perversion, bringing a contradiction and ambiguity. The term perversion is often seen as heavy, linking the idea of being that which is not the main and the non-genital. Thus, the present paper aims to demonstrate what Freud’s texts can still oppose the misunderstandings that are still committed in relation to his works. In order to reach the proposed objectives, a bibliographical research was done. The results obtained were that: according to Freud, homosexuality is a choice of sexual object, being either a choice of a heterosexual object; Homosexuality in the same way that heterosexuality happens to be a sexual practice located in any of the clinical structures; And according to Lacan every human being can situate from one side or the other the sharing of the sexes, regardless of the genetic, hormonal, anatomical or social sex.